تعليم مهارة القراءة باستخدام أسلوب Cooperative Integrated Reading and Composition (CIRC) بوسيلة Lumio by SMART - Fajriah; Cut Fathin Husna; Herni Julita (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
Based on observations conducted by the researcher at MTsN 1 Banda Aceh, the researcher found that some students have difficulty accurately understanding Arabic texts, which leads to a decline in their participation and engagement in the teaching and learning process. This problem is linked to the lack of diversity in teaching methods and the limited use of interactive educational tools. The objectives of this study are to determine the effectiveness of using the CIRC method with the Lumio by SMART tool in teaching reading skills at MTsN 1 Banda Aceh. In this study, the researcher employed an experimental research method using a One-Group Pre-test Post-test Design. To collect data, the researcher utilized pre-tests and post-tests. The results of the study indicate that teaching reading skills using the CIRC method with the Lumio by SMART tool is effective in teaching reading skills. The researcher found that the Paired Sample T-Test yielded a significance level (Sig., 2-tailed) of 0.00, which is smaller than the significance level of 0.05, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.